Strategic Conditions for Effective Management of Workers’ Competitiveness in the Agro-Food Sector of the Russian Federation - RUBTSOVA, Vera Nikolayevna; ANDRYUSHCHENKО, Sergey Anatolevich; SHARIKOVA, Irina Viktorovna; SHARIKOV, Artem Viktorovich; GOVORUNOVA, Tatyana Vladimirovna (Journal of Environmental Management and Tourism, 2019)
The article analyses the competitiveness rural working age population of Russia employed in the agro-industrial complex. The authors conclude that their competitiveness does not answer the challenges posed by current development of Russian agro-industrial complex. This situation is caused by the absence of an integrated strategic governmental approach to the creation of conditions for the rise of the competitiveness of rural population of working age employed in the agro-industrial complex of the Russian Federation, both in a whole and in regional agro-industrial complexes. Authors propose particular measures to increase the efficiency of governmental management of the competitiveness of rural working age population employed in Russian agro-industrial complex: to create conceptual, legal, organizational and strategic conditions that would ensure concentration and goal-directed disposal of resources in this area. Analysis of the results of the sociological survey conducted by the Federal State Statistics Service of the Russian Federation allowed to distinguish threshold indicators of significant social factors of competitiveness: health self-assessment and active lifestyle abilities of the rural working age population employed in Russian agro-industrial complex. Threshold indicators used in the current state programs will help clarify the goals and select priorities for a state competitiveness management policy for rural working age population employed in the agro-industrial complex of the Russian Federation.